VULNERACIÓN DEL DERECHO A LA INFORMACIÓN PÚBLICA EN EL ACCESO A LAS BASES DE DATOS ESTATALES - Novoa León, Karen Gabriela (2017)
The present research work analyse the infringement of the right of access to information of peruvian citizens, made by public institutions, when denying access to the institutional e-mails of public workers. According established in Mayorga v. Gamarra (file N° 36677-2014-0-1801-JR-CI-05) case, the court ordered delivering the institutional e-mails of the minister of Peru Eleodoro Mayorga Alba to the Peruvian citizen Marco Gamarra Galindo, in the period in which Mayorga was Minister of Energy and Mines. During the development of this research, was necessary the study of: The Political Constitution of Peru, The Law on Transparency and Access to Public Information, its Regulation, jurisprudence of the Constitutional Court, etc.; making a viable review of the main principles that inspire the right of access to public information and a broad knowledge on how the exercise of this right in Peru is guaranteed. In the Comparative Law, we analysed the rules of the legislations of USA, Mexico and Chile; countries where is difficult to access public workers e-mails, also we analysed how this problem was solved. It is important to note that the Organization of American States (OAS) and The United Nations (UN) have contributed greatly to the development of this right. The first part of this research develops the methodology, which contains the problem, general and specific objectives, justification, methods and techniques of data collection and research. The second part contains seven chapters, where develops the right of access to information; the exercise of the right of access to public information in Peru; the right to privacy and to the private life; the right to inviolability of communications; the e-mail of the public worker; and e-mail publicity in Comparative Law Finally, the third part presents the results, discussions, conclusions and recommendations; where we exposed the transgression that the entities of the public administration are doing, and the affectation to the fundamental right of access to public information are exposed.